Autonomous Province of Vojvodina between Constitution and Assessment of Serbian Constitutional Court - Čiplić, Svetozar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The author deals individual assessments Constitutional court of the Competent im Law, as well as its different interpretation of constitutional and legal provisions. The author is of the opinion that the Constitutional Court amended the constitution and the law guaranteed the position of the Autonomous Province of Vojvodina and that the "conservative interpretation of" diminished the rights of citizens by the constitution itself by.